PENGARUH TECHNOLOGY ADOPTION TERHADAP TECHNOSTRESS DENGAN EMPLOYABILITY SEBAGAI VARIABEL MODERASI PADA TENAGA KERJA INDONESIA - Theresia Ivana Pratiwi; Angela Caroline; Agus Gunawan; Yoke Pribadi Kornarius (Media Bina Ilmiah, 2025)
The digital transformation in Indonesia has led to increased technology usage in the workplace, but it has also contributed to rising levels of technostress. This study aims to examine the effect of Technology Adoption on Technostress, with Employability as a moderating variable. A quantitative approach was employed using Moderated Regression Analysis (MRA), based on data collected from 176 Indonesian workers. The results indicate that both Technology Adoption and Employability have a direct positive impact on Technostress. However, their interaction shows a negative and significant effect, suggesting that Employability moderates and reduces the impact of Technology Adoption on Technostress. In conclusion, Employability plays a crucial role in helping workers manage technological pressure, highlighting the importance of enhancing digital skills and adaptability in the modern workforce.